Evaluation of Patient-Reported Outcomes in Burn Survivors Undergoing Reconstructive Surgery in the Rehabilitative Period. Issue 1 (July 2020) - Sheckter, Clifford C.; Carrougher, Gretchen J.; McMullen, Kara; Bamer, Alyssa; Friedstat, Jonathan; Pham, Tam N.; Gibran, Nicole S.
Abstract : Background: Health-related quality of life is decreased in burn survivors, with scars implicated as a cause. The authors aim to characterize the use of reconstructive surgery following hospitalization and determine whether patient-reported outcomes change over time. The authors hypothesized improvement in health-related quality of life following reconstructive surgery. Methods: Adult burn survivors undergoing reconstructive surgery within 24 months after injury were extracted from a prospective, longitudinal database from 5 U.S. burn centers (Burn Model System). Surgery was classified by problem as follows: scar, contracture, and open wound. The authors evaluated predictors of surgery using logistic regression. Short Form-12/Veterans RAND 12 health survey outcomes at 6, 12, and 24 months were compared at follow-up intervals and matched with nonoperated participants using propensity score matching. Results: Three hundred seventy-two of 1359 participants (27.4 percent) underwent one or more reconstructive operation within 24 months of injury. Factors that increased the likelihood of surgery included number of operations during index hospitalization ( p < 0.001), hand ( p = 0.001) and perineal involvement ( p = 0.042), and range-of-motion limitation at discharge ( p < 0.001). Compared to the physical component scores of peers who were not operated on, physical component scores increased for participants undergoing scar operations; however, these gains were only significant for those undergoing surgery more than 6 months after injury ( p < 0.05). Matched physical component scores showed nonsignificant differences following contracture operations. Mental component scores were unchanged or lower following scar and contracture surgery. Conclusions: Participants requiring more operations during index admission were more likely to undergo reconstructive surgery. There were improvements in Short Form-12/Veterans RAND 12 scores for those undergoing scar operations more than 6 months after injury, although contracture operations were not associated with significant differences in Short Form-12/Veterans RAND 12 scores.